MICROESTRUTURA DE PÊLOS-GUARDA DE MAMÍFEROS NÃO VOADORES (MAMMALIA) - Dias, Douglas de Matos; Matos, Ana Paula Dantas Messias de; Ribeiro, Adauto de Souza (Revista Nordestina de Zoologia, 2012)
The microstructure identification of guard hairs in mammals, has plenty applications in taxonomy, biology’s conservation and carnivorous’ diet. In this study we’ve analyzed guard hairs samples of ten morphospecies of no flying mammals, two alive individuals of the domestic species Canis lupus familiaris and Felis catus and eight wild taxidermized species in the UFS taxidermy laboratory: Callithrix jacchus, Cerdocyon thous, Cuniculus paca, Euphractus sexcinctus, Galictis sp., Mazama sp., Sylvilagus brasiliensis e Tamandua tetradactyla. Six cuticles patterns of guard hairs were described, being the transverse wave pattern with the ornamented scales’ edges similar between Canis lupus familiaris, Cerdocyon thous and Tamandua tetradactyla and the irregular wave pattern in common between Cuniculus paca, Mazama sp. and Galictis sp. Seven patterns were identified at medullary hairs structure, noted that Felis catus and Galictis sp. share the "trabecular" pattern and the orders representative Cingulata and Pilosa does not have marrow in their hairs.